The Development of Natural Knowledge Science Learning Module to Improve Student Learning Achievement in Primary School - Sarjana Sarjana; Fadillah Fadillah; Indri Astuti (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to describe (1) the design of the development module for the preservation of living natural resources in the study of natural science; (2) the process of developing modules for the conservation of living natural resources in the learning of natural science; and (3) student learning about the preservation of living natural resources in the learning of Natural Sciences in the fourth grade of SD Negeri 01 Hulu Sungai. This research is descriptive qualitative research to study "the development of learning modules with data collection techniques for interviews, observation, document study. Data analysis techniques ranging from display data, data reduction, data reflection, and conclusions. The results showed that (1) the design of the development module of the preservation of living natural resources material in the learning of Natural Sciences in the form of a front cover with pictures of students studied, preface, table of contents, list of images, concept framework, introduction, instructions for use of modules, competence content, basic competencies, learning activities 1,2,3 and 4, summary, and evaluation, student worksheets, detailed answers, glossary, bibliography, list of life forms; (2) the process of developing modules for the preservation of living natural resources in the learning of Natural Sciences is carried out with the following steps: a). Research and data collection; b). Planning c). Development of learning modules; d). Expert validation; e). Product trial; and (3) all students can achieve their learning achievement in science learning with the development of learning modules with the highest grades of 90 and the lowest scores of 78.